Restitusi sebagai Bukti Pertobatan: Studi Lukas 19 tentang Zakheus dan Relevansinya bagi Koruptor - Sinambela, Juita Lusiana; Tamba, Gerbin; Sinaga, Janes (Jurnal Teologi Kontekstual Indonesia, 2024)
This study aims to deepen the understanding of Zacchaeus' life transformation based on the narrative of Luke 19 in the context of everyday life. Using a descriptive qualitative research method, this study leads to an in-depth analysis of Zacchaeus' character, actions, and responses, including the social and moral context surrounding his work as a chief tax collector. This study analyzes the biblical text to gain an in-depth understanding of Zacchaeus' changes in attitude and behavior after interacting with Jesus. Through this approach, the study aims to highlight the impact of the encounter with Jesus on Zacchaeus' daily life, his repentance response, and how these changes affect his social interactions. One of the main aspects of Zacchaeus' repentance is restitution, namely the return of rights to those who have been harmed, which is a clear evidence of his moral and spiritual transformation. This study also links the principle of restitution in the story of Zacchaeus with its relevance to corruption cases in the modern era, emphasizing the importance of restoring justice as part of true repentance. The results of this study are expected to contribute to a more comprehensive understanding of Zacchaeus' life transformation process, including internal and external changes, as well as its positive impact on his social environment. Thus, this study is not only a theological study, but also has practical relevance in the context of daily life and moral values. This study reflects the comprehensiveness and relevance in understanding the transformation of life based on the story of Zacchaeus' conversion in Luke 19, as well as its implications for the practice of restitution in various social contexts, including in cases of abuse of office and corruption.